“I feel like it gets worse as I get older”: perspectives of peri-postmenopausal women with PCOS - Pamela J. Wright; Cynthia F. Corbett; Robin M. Dawson; Charlotte Burts (Frontiers in Global Women's Health)
IntroductionPolycystic ovary syndrome (PCOS) is a chronic endocrinopathy that transcends the reproductive years. Peri-postmenopausal women with PCOS remain at cardiometabolic risk or subsist with established comorbidity while continuing to contend with persistent PCOS signs and symptoms such as hirsutism. Evidence based information for peri-postmenopausal women with PCOS is scant. The purpose of this qualitative study was to explore the physical, psychosocial, and healthcare perspectives of peri-postmenopausal women with PCOS.MethodsPeri-postmenopausal women with PCOS aged ≥43 years (n = 29) were recruited using ResearchMatch to participate in a virtual interview. Interviews were conducted using a semi-structured guide. The interviews were transcribed, de-identified, and analyzed using the steps of reflexive thematic analysis.ResultsParticipants were aged 52.5 (±6.6) years, mostly White (69.0%), and highly educated with 62.0% having at least a college degree. In terms of health, most participants were perimenopausal (n = 20; 69.0%), categorized as “obese” (BMI ≥30) (n = 20, 69%), had ≥3.0 comorbidities (n = 26; 90%), and took ≥5 prescribed medications (n = 17; 58.0%). Five overall themes were identified: (1) Déjà vu?, (2) Sociocultural Stigma, (3) Trauma Experiences, (4) Self-Advocacy, and (5) Resilience vs. Resignation.DiscussionThe identified themes highlight the need for a more proactive, trauma-informed, culturally tailored healthcare approach that provides education and support in managing PCOS over the lifespan. Women's needs include resources after adverse pregnancy outcomes and routine screening of emotional health, with subsequent treatment when indicated. The findings indicate a need for healthcare provider communication and sensitivity training. Women with PCOS could benefit from advocacy and resilience training. As a relatively unexplored area of women's health, more research is needed to address the needs of older women with PCOS and develop and test programs that train healthcare providers to deliver patient-centered care and equip women with the information and resources to properly manage PCOS and cop effectively over their life course.